Protective effect of an antithyroid compound against γ-radiationinduced damage in human colon cancer cells - Perona, Marina (2014)
We have previously reported the radioprotective effect of propylthiouracil (PTU) on thyroid cells. The aim of the present study was to analyze whether tumor cells and normal cells demonstrate the same response to PTU. Human colon carcinoma cells were irradiated with γ-irradiation with or without PTU. We evaluated the clonogenic survival, intracellular reactive oxygen species levels, catalase, superoxide dismutase and glutathione peroxidase activities, and apoptosis by nuclear cell morphology and caspase-3 activity assays. Cyclic AMP (cAMP) levels were measured by radioimmunoassay. PTU treatment increased surviving cell fraction at 2 Gy (SF2) from 56.9 ± 3.6 in controls to 75.0 ± 3.5 (p<0.05) and diminished radiation- induced apoptosis. In addition, we observed that the level of antioxidant enzymes’ activity was increased in cells treated with PTU. Moreover, pretreatment with PTU increased intracellular levels of cAMP. Forskolin (p<0.01) and dibutyryl cAMP (p<0.05) mimicked the effect of PTU on SF2. Co-treatment with H89, an inhibitor of protein kinase A, abolished the radioprotective effect of PTU. PTU reduces the toxicity of ionizing radiation by increasing cAMP levels and also possibly through a reduction in apoptosis levels and in radiation-induced oxidative stress damage. We therefore conclude that PTU protects both normal and cancer cells during exposure to radiation in conditions mimicking the radiotherapy.